The role of global warming trend and tropical interannual variability as drivers of South America’s 2022–2024 climate extremes - Leonardo Mamani; Wallace Cevalho; Renato Trevisan Signori; Itamara Parente de Souza; Mary Toshie Kayano; Jorge Molina-Carpio; Rodrigo Augusto F. de Souza; Jhan-Carlo Espinoza; Rita V. Andreoli (Climate Dynamics, 2026)
From 2022 to 2024, South America experienced unprecedented regional climate extremes with severe socioeconomic impacts. These included extreme anomalies in temperature and precipitation, causing extreme drought conditions in southeastern South America and the Altiplano during spring 2022; extreme fire weather in central Chile in summer 2023; flooding in Rio Grande do Sul during autumn 2024; and the multiyear Amazon drought persisting throughout the springs 2022–2024. While these events were linked to the Global warming trend (GWT), Tropical interannual variability (TIV), and synoptic-scale processes, their contributions need to be clarified. Using linear regression, we decomposed the observed climate anomalies during 1998–2024 into GWT and TIV components and derived a Residual component representing anomalies not explained by either. This approach clarifies, through seasonal spatial patterns and contributions from regional variance, the roles of GWT and TIV in observed climate extremes across South America. From spring 2022 to spring 2024, GWT exhibited a strong background warming anomaly, while TIV displayed unusually robust teleconnections, particularly during its positive phases. As a result, a significant part of precipitation variability associated with climate extremes across the continent was driven by TIV, whereas GWT dominated in central-southern Chile. Both TIV and GWT contributed substantially to widespread South American warming, with GWT becoming the dominant influence as TIV weakened, except in central-southern Chile, where other factors prevailed. The unprecedented concurrence of strong GWT and combined TIV forcing amplified and prolonged climate extremes across the continent. The framework presented here can support climate extremes attribution worldwide.